The development of protection activities for Chinese architectural heritage and its unique conservation concepts - Jin, Xuan (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The historic architectural heritage of different regions has unique construction methods due to different geographical characteristics and cultural backgrounds. The methods of maintenance applied to them are also wide ranging. China’s historic woodframed architecture has its own characteristics, very different from that of Western architecture. The craftsmen who work on these structures have accumulated a wealth of conservation concepts and techniques suitable for Oriental architectural features over time. With the introduction of international heritage conservation policy, the Chinese government has developed its own conservation principles. These principles were adapted from international policies to suit traditional Chinese conservation experience, forming unique concepts of authenticity and integrity, as well as different conservation methods where necessary. The purpose of this paper is to introduce the development of Chinese architectural heritage conservation policy and analyse unique conservation concepts according to architectural heritage characteristics, as well as to highlight problems which China’s architectural heritage has faced
Keywords: dziedzictwo architektoniczne; Chiny; działalność ochronna; koncepcje konserwatorskie